2012
DOI: 10.1002/term.1646
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel akermanite:poly-ϵ-caprolactone scaffolds for human adipose-derived stem cells bone tissue engineering

Abstract: In this study, three different akermanite:poly-ϵ-caprolactone (PCL) composite scaffolds (wt%: 75:25, 50:50, 25:75) were characterized in terms of structure, compression strength, degradation rate and in vitro biocompatibility to human adipose-derived stem cells (hASC). Pure ceramic scaffolds [CellCeram™, custom-made, 40:60 wt%; β-tricalcium phosphate (β-TCP):hydroxyapatite (HA); and akermanite] and PCL scaffolds served as experimental controls. Compared to ceramic scaffolds, the authors hypothesized that optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 50 publications
0
47
0
Order By: Relevance
“…PCL was chosen as a scaffold for this study as it has previously been shown to have little impact on hASC differentiation, providing a convenient method to isolate the osteogenic activity of the PC-miR-148b–SNP photoactivated conjugate without osteogenic substrate effects [24]. The defect partially healed with the photoactivated conjugates while the control groups had minimal healing and remained opened even after 12 weeks, further verifying the model and the size of the non-healing defect.…”
Section: Discussionmentioning
confidence: 79%
“…PCL was chosen as a scaffold for this study as it has previously been shown to have little impact on hASC differentiation, providing a convenient method to isolate the osteogenic activity of the PC-miR-148b–SNP photoactivated conjugate without osteogenic substrate effects [24]. The defect partially healed with the photoactivated conjugates while the control groups had minimal healing and remained opened even after 12 weeks, further verifying the model and the size of the non-healing defect.…”
Section: Discussionmentioning
confidence: 79%
“…Several common synthetic polymers have been used to form composites with DCSCs, including polycaprolactone (PCL), poly(glycolic acid) (PGA) and poly(lactic-co-glycolic acid) (PLGA). Porous PCL-akermanite scaffolds (~90% porosity, ~100 µm pore size) were fabricated by loading akermanite powder into the PCL matrix at different weight ratios [121]. The highest compressive strength was attained at 25 wt % loading of akermanite particles (~10 MPa), compared to the other groups (50 wt % loaded, 75 wt % loaded, and PCL control) which all exhibited similar strengths (~4.3 MPa).…”
Section: Development Of Dcscs For Broader Clinical Applicationsmentioning
confidence: 99%
“…This was indicated by high alkaline phosphatase (ALP) activity, osteocalcin expression, and mineralization [31]. Using akermanite-based scaffolds, Zanetti and colleagues [32] have shown that ADSCs cultured for 21 days in osteogenic medium before seeding them on the scaffold have greater calcium deposition and osteocalcin expression and low IL-6 expression, compared with cells seeded on polycaprolactone-β-tricalcium phosphate. In an interesting study by Fröhlich and colleagues [33], ADSCs seeded on decellularized native bone scaffolds which provided the necessary structural and mechanical environment for osteogenic differentiation showed increased construct cellularity and elevated amounts of bone matrix components (collagen, bone sialoprotein, and osteopontin).…”
Section: Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%